Antibacterial activity and phytochemical screening of erythrina fusca lour. leaf extract (fabaceae) / Adiez Sapura Azmi ... [et al.] - Azmi, Adiez Sapura; Amini, Mohammad Humayoon; Syakir Nor Azman, Muhammad Farhan; Salim, Fatimah (Universiti Teknologi MARA, 2022)
Erythrina fusca Lour. (Family Fabaceae) is a flowering tree, locally known as ‘Chengkering’. The plant is traditionally used in the treatment of some symptoms related to bacterial infections such as skin itching and inflammations as well as on wounds. This work reports for the first time on the in vitro antibacterial activity of methanolic leaf extract of E. fusca against some common bacterial strains such as Klebsiella pneumonia, Proteus vulgaris, Pseudomonas aeruginosa, Bacillus cereus, Bacillus subtilis, and Staphylococcus aureus. The in vitro antibacterial assay was carried out using agar well diffusion method with the extract concentration of 3 mg/well and vancomycin 30 μg/well as the positive control. Except for K. pneumonia, it was found that the extract exhibits antibacterial effects against all the tested bacterial strains with the zone of inhibition (ZOI) in a range of 10.5 – 14 mm. Based on the preliminary phytochemical screening using standard qualitative phytochemical tests, the leaf extract contains a significant number of alkaloids, flavonoids, terpenoids, and tannins, which might contribute to its antibacterial activity. Both antibacterial properties and the presence of various phytochemicals in the extract could support the traditional uses of E. fusca in treating symptoms related to bacterial infections. The findings would serve as a basis for further exploration of the antibacterial potential of the plant’s leaves.